Twenty years of illustration awards for children’s and young adults’ books in Spain - Gómez Díaz, Raquel; Rodríguez, Araceli García (Revista General de Información y Documentación, 2022)
In recent decades, illustration in children’s and young adults’ books has become especially important as a communicative and educational element. This has led to a proliferation of illustrated books and albums, as well as to an increase in the number of prizes and awards for them. This development has given the figure of the illustrator greater prominence and serves as an instrument for promotion and visibility, as well as a stimulus to production. Accordingly, the objective of this article is to set out the characteristics of Spanish children’s and young adults’ book awards focused on illustration within the 2000–2020 period, indicating their chronology, their organizers, the illustrators who have received the most awards, the thematic categories that are most commonly represented and the prize types and sums awarded to winners. To this end, a list of 103 Spanish children’s and young adults’ literature awards was compiled; 22 of these are specifically for illustration. The conclusion was reached that Spanish publishers are opting for illustrated books and albums that they themselves have produced. It was also found that such awards have consolidated over time, are normally of an institutional nature and offer small financial sums. Moreover, all kinds of thematic categories are represented in these awards, though fictional prose works clearly predominate, and within this category, awards most commonly go to illustrated albums.
Keywords: Children’s and young adults’ literature illustrations awards; Children’s and young adults’ literature illustrators; Children’s and young adults’ literature; Children's and youth adults’ illustrated books; Picture Books; Literature awards